Systematic revision and cladistic analysis of Epiphragmophora Doering from Argentina and southern Bolivia (Gastropoda: Stylommatophora: Xanthonychidae) - Cuezzo, Maria Gabriela (2006)
As a first step towards a comprehensive revision of the South American genus Epiphragmophora Doering 1874, taxa described from Argentina and Bolivia, inhabitants of the rainforest Yungas (Amazonian biogeographic subregion) Monte, Pre-Puna biogeographic provinces and Chacoan biogeographic subregion are studied. Special attention has been paid to the morphology of the terminal genitalia with respect to its relevance for systematics. The revision is based on the examination of nearly all type material, plus extensive field work and examination of additional material deposited in several Museums. Shell, pallial system and genitalia of each species have been described and illustrated, some of them for the first time. Detailed description on the structure and connections of the dart sac apparatus and associated mucous glands in the terminal genitalia in each species is provided. A total of twenty-four species plus three new ones for the science are described from the region. From the total number of species, the anatomy of seven species of them is described for the first time. Six unambiguous synapomorphies support the monophyly of the genus: body whorl surface malleated with diagonal ribs (character # 1 [2]), umbilicus overlapped but not solded to body whorl (character # 2 [1]), peristome thick, wide reflexed (character # 4[1]), mucous glands unequal in size and shape (character # 15 [1]), insertion of mucous glands ducts in middle portion of dart sac (character # 17 [1]), penial retractor muscle inserting in medial epiphallus (character # 23 [1]). Most of the synapomorphies of the generated phylogenetic hypothesis are characters from the genitalia, shell characters proved to be less informative. The short duct of the bursa copulatrix, a character that traditionally had been used to define the genus is characteristic only of a small group of species.  The distribution of the Argentinean species studied is illustrated on maps according to the biogeographic areas. An area cladogram based on the cladistic analysis is presented. According to this hypothesis the species inhabitants of the Yungas biogeographic province are basal groups of the remaining species inhabitants of the Chacoan, Monte and Pre-puna regions. The Monte and Pre-puna species conform a monophyletic clade. The biogeographic relationships are in agreement to former studies on Latin-American entomofauna (Morrone, 2006).